Microplastics and Heavy Metals Contamination in Agricultural Soils Near the Landfill: A Case Study in Yogyakarta, Indonesia: english - Lestari, Puji; Baihaqi, Muhammad Farid; Wacano, Dhandhun; Amalia, Almira Nur (Teknik Lingkungan Universitas Islam Indonesia, 2026)
The Piyungan landfill in Yogyakarta, Indonesia, is a potential source of environmental pollution, releasing contaminants such as microplastics and heavy metals that can accumulate in the nearby soils. Agricultural soil surrounding the landfill has been found to contain both types of pollutants. The coexistence of microplastics and heavy metals may influence their environmental mobility and toxicity, potentially posing risks to ecosystems and human health. This study investigates the co-occurrence of microplastics and heavy metals (Pb and Cd) in agricultural soils near the Piyungan landfill. Soil samples were collected from four different points around the site. Microplastic extraction involved wet peroxide oxidation (WPO) using 30% H₂O₂, followed by density separation with saturated NaCl. The isolated microplastics were analyzed under a microscope, and polymer types were identified using Fourier Transform Infrared Spectroscopy (FTIR). Concentrations of Pb and Cd, both within the soil matrix and associated with microplastics, were measured using Atomic Absorption Spectrophotometry (AAS). The abundance of microplastics in the soil ranged from 3450 to 5110 particles/kg, consisting of fragments, films, foams, fibers, and pellets in various colors. Detected polymers included polypropylene (PP) and polyethylene (PE). Lead concentrations ranged from 5.1 to 8.4 mg/kg, while cadmium concentrations ranged from 0.6 to 1.4 mg/kg. These levels were significantly higher than those found in the reference soil, indicating the contamination of both microplastics and heavy metals in the agricultural soils near the landfill. Both heavy metals were also detected in microplastics. The observed co-contamination underscores the potential for complex interactions between microplastics and heavy metals in the soil near landfill, which may enhance their transport and combined toxicity.